2022
DOI: 10.1021/acs.iecr.2c02570
|View full text |Cite
|
Sign up to set email alerts
|

Aldol Condensation of Methyl Propionate and Formaldehyde: Thermodynamics, Reaction Process, and Network

Abstract: The aldol condensation of methyl propionate (MP) and formaldehyde (FA) is an environmentally friendly and sustainable route to produce methyl methacrylate (MMA). However, the side reaction is a huge barrier to achieving high selectivity to the target product. To strengthen the regulation of selectivity for the main reaction, a reaction network was established based on the validation and analysis of side reactions in the system through a combination of experimental and computational methods. The thermodynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…This finding implies that the number of medium acid sites matters for aldol condensation, in particular, in terms of yield, and that the elevated activity was achieved by the occurrence of multiple medium acid sites on the surface of the catalyst. On the other hand, there are small amounts of strong acid sites that exist on the 5Cs-5Nb/Al 2 O 3 catalyst, which may lead to the creation of unwanted byproducts and exacerbate carbonaceous deposits on its surface. ,, It is concluded that acid–base sites exhibit a synergetic catalytic effect in aldol condensation, and tuning the balance of the acid–base sites can effectively improve the activity of the catalysts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding implies that the number of medium acid sites matters for aldol condensation, in particular, in terms of yield, and that the elevated activity was achieved by the occurrence of multiple medium acid sites on the surface of the catalyst. On the other hand, there are small amounts of strong acid sites that exist on the 5Cs-5Nb/Al 2 O 3 catalyst, which may lead to the creation of unwanted byproducts and exacerbate carbonaceous deposits on its surface. ,, It is concluded that acid–base sites exhibit a synergetic catalytic effect in aldol condensation, and tuning the balance of the acid–base sites can effectively improve the activity of the catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, there are small amounts of strong acid sites that exist on the 5Cs-5Nb/Al 2 O 3 catalyst, which may lead to the creation of unwanted byproducts and exacerbate carbonaceous deposits on its surface. 51,58,59 It is concluded that acid−base sites exhibit a synergetic catalytic effect in aldol condensation, and tuning the balance of the acid−base sites can effectively improve the activity of the catalysts.…”
Section: Catalytic Performance and Reusability Studiesmentioning
confidence: 99%